The reading practices of people with neuropsychiatric disabilities: a review of library and information science literature - Katarina Hagberg; Karin Lundin; Anna Lundh; Åse Hedemark (Information Research: An International Electronic Journal)
Introduction. The ability to read and interpret different types of text can be significantly impacted by neuropsychiatric disabilities, which affect cognitive abilities. This paper explores and reviews previous studies within library and information science on neuropsychiatric disabilities in relation to reading practices.